STRATEGI PELIBATAN PEMUDA DALAM PENGEMBANGAN USAHA BUDIDAYA KERAMBA JARING APUNG DI TELUK AMBON DALAM - Mirsya Sahuleka; Yolanda MTN Apituley; Dion Bawole (Universitas Pattimura, 2020)
Areas that have potential in the development of Keramba Jaring Apung (KJA) cultivation business are Waiheru Village and Poka Village. The village is located near the waters of Teluk Ambon Dalam which has been designated as a development for marine cultivation activities with the Keramba Jaring Apung (KJA) system in ambon city spatial plan in 2011-2031. the lack of interest in young people to dive into the world of fisheries is something to be aware of. Young people's interest in working in fishing businesses is waning, job opportunities and businesses in other sectors are the reason young people are declining interest in jobs as fish grower. The purpose of the research is to know the role of youth in the cultivation of Keramba Jaring Apung in Teluk Ambon Dalam and to design youth engagement strategies in the cultivation of Keramba Jaring Apung in Teluk Ambon Dalam. The research method uses qualitative deskritif analysis and SWOT analysis. Based on the results of youth engagement research in the cultivation of Keramba Jaring Apung in Teluk Ambon Dalam is very minimal. An alternative youth engagement strategy that can be implemented is the SO strategy.